ROLE OF CHEMOATTRACTANT CHEMOKINE (SDF-1/CXCR4) IN BONE MARROW NICHE - Dyah Indartin Setyowati; Zahreni Hamzah (UPT Penerbitan Universitas Jember)
Bone marrow is the pioneer for studying stem cells.The basic concept of stem cells obtained by studyinghematopoietic stem cells. Although how theinteraction of HSCs with the local environmentnecessary for the maintenance of stem cells can notbe fully explained ( Compston, 2002; Iwasaki andSuda., 2010). Studies of HSCs aims to study thehabits of these cells in a population of cellscontained in bone marrow . So far little is knownabout the interaction of the bone marrow niche. Thestudy was conducted using a culture system thatlimited done in a sustainable way to prove theinteraction of the bone marrow niche. From theseresults can then be identified subset of osteoblasts (N-Cadherin + CD 45-) that physically attaches to theHSCs in the BM . ( Tong Yin , 2006)Bone marrow consist of hematopoietic cells arewrapped by the bone structure. Hematopoietic cellsdevelop in the bone cavity and retained in the bonemarrow until they have matured, then released intothe vascular system ( Yin and Li , 2006). Most cells ofhaemopoietic can be found next to the endostealsurface of the bone, which layer is primarilyosteoblasts. Osteoblasts is one type of bone cell thatserves to reform or bone formation. HSCs are stemcells that are known to differentiate into osteoclasts.Osteoclasts are the cells of bone that serves to boneresorption. Their physical proximity betweenosteoblasts and which HSCs are parent cellsosteoclasts, as well as the identification of N -Cadherin / β - Catenin adherent complex betweenthe two prove their relationship or communicationbetween these cells. Osteoblast cells not only play arole in bone formation, but as osteoblast niche inthe bone marrow also, contribute to themaintenance of HSCs that are stem cells osteoclasts(Yin and Li , 2006 ; Tong Yin , 2006 ).There are two main types of stem cells areembryonic and adult stem cells . Pluripotentembryonic stem cells derived from the inner cellmass of blastocysts and has the ability to be a threeembryonic germ layers , namely ectoderm ,endoderm , and mesoderm (Li and Xie , 2005). Atbirth, adult stem cells including GSCs and SSCs willoccupy and live in a special microenvironment,called a niche (Li and Sie., 2005)Niche is different depending on the type of tissue ororgan. Structurally niche supported by the cells andtheir interactions molecular signals that preparedand provided to form a microenvironment for stemcells. Niche hypothesis has actually been describedby Scofield in 1978 ( Li and Sie , 2005; Yin and Li ,2006) . Stem cell niche is supported by manysignaling and adhesion molecules involved in theinteraction of the stem cell niche, accounted diversecharacteristics for each niche function ( figure 1 )that is; SDF -1/CXCR4 , SCF/c - Kit, Jagged/Notch,angiopoietin-1/ Tie2 ( Ang-1/Tie2 ), and Ca2 + -sensing receptor ( Yin and Li, 2006). Most studiesconducted to know and understand the molecularmechanisms of interaction and behavior of stemcells. Understanding the interaction and behavior ofstem cells in the bone marrow niche is veryimportant to understand the eventsosteoclastogenesis, especially how osteoclastprecursor cells can be recruited from niche thenmobile until homing (Kollet et al , 2007). Research isusually conducted in diseases associated with theaccumulation of osteoclasts or osteoclast progenitorcells that causes pathological osteolysis , such as ;benign bone tumors and bone metastases cancer (Kollet et al , 2007; Jennifer , 2009).